PENGARUH PEMBERIAN DARK CHOCOLATE TERHADAP PENURUNAN TINGKAT DISMENORE PADA REMAJA PUTRI - Rika Hidayanti; Alfiah Rahmawati; Emi Sutrisminah (Jurnal Maternitas Kebidanan, 2022)
ABSTRACT Adolescence is a period of changes in development and growth both physically and psychologically, especially in the maturity of the reproductive organs of adolescent girls. Not a few who experienced uncomfortable conditions at that time. One of them is due to dysmenorrhea or pain during menstruation which can interfere with learning activities and concentration. To describe information about the effect of giving dark chocolate to adolescent girls to decrease the level of dysmenorrhea. Non-systematic literature study research and searching for articles using the PubMed, DOAJ and Google Scholar databases. Obtained 20 articles, of which there are 5 international articles and 15 national articles, which are in accordance with the topic and have been considered in the criteria: Adolescent girls who experience dysmenorrhea are given therapy dark chocolate. Shows a change in the decrease in the level of dysmenorrhea during menstruation after therapy is given dark chocolate to adolescent girls. Has a good effect in reducing the level of pain during menstruation in adolescent girls. Keywords: adolescent, dark chocolate, dysmenorrhea